Thermal And Mechanical Behaviour Of Recycled Polypropylene/Polyethylene Blends Of Rejected-Unused Disposable Diapers - Muhd Ridzuan Mansor, Muhd Ridzuan; Taufiq, M.J.; Mustafa, Zaleha; Jumaidin, Ridhwan; Mohammad Taha, Mastura; Firdaus, Firdaus, H. M.S.; Basori, Basori (Penerbit Universiti Teknikal Malaysia Melaka, 2019)
This paper presents the characterization of recycled plastic that derived from the rejected-unused disposable diapers containing polypropylene (PP) and polyethylene (PE), noted as r-PP/PE. The blends were tested for thermal, mechanical and morphological properties. Tensile test showed that the r-PP/PE is lower in strength and strain but higher for modulus in comparison to the v-PP/PE by 56%, 55%, and 2% respectively. For the flexural properties, the r-PP/PE also has lower in strength, strain, and modulus as 67%, 13%, and 77% respectively. Lower absorbed energy and impact strength was observed in r-PP/PE, 36% and 24% respectively compared to v-PP/PE. Thermal analysis revealed that the degree of crystallinity of recycled PP and PE was 19% and 20% lower than the virgin possibly due to thermal degradation during the process. Morphological examination revealed the present of impurity, phase separations and inhomogeneity were found in the r-PP/PE as compared to v-PP/PE that might contribute to their lower strength.